Aplicativo móvil para el autoconocimiento y desarrollo de habilidades en lengua huitoto murui de los niños de la Comunidad Nativa “Centro arenal” - Cenepo Saquiray, Gin Paoll (2024)
The objective of this research work is to improve self-knowledge and development of skills in the Huitoto Murui language through the use of a mobile application, for which the evaluation of self-knowledge and development of skills in the Huitoto Murui language was carried out. It is intended that this application called Urutiko (children in Huitoto Murui) is aimed at facilitating learning from an early age of aspects related to personal development (self- knowledge), skills, competencies to interact, contextualized in the Huitoto Murui language, which the question to be resolved is: How will the mobile application improve the self-knowledge and development of skills in the Huitoto language of the children of the native community “Centro Arenal”? This work has used the Observation Sheets to record the data in the experiments. The work is an Applied Type research, with a Quasi-Experimental design. It has been found that the results obtained in the tests have shown a higher percentage in the use of the mobile application over traditional teaching. Finally, it was concluded that this work allows us to affirm that the development of a mobile application can improve self-knowledge and development of skills in the Huitoto Murui language, based on the results obtained in tests with children between 3 to 7 years of school age from the “Centro Arenal” native community is favorable for the learning of children of initial and primary school age.